2011
DOI: 10.1007/s00264-011-1451-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical tibiofemoral angle and body mass index in normal Nigerian children

Abstract: Purpose The tibiofemoral angle (TFA) is a reliable tool for determining lower-limb axial alignment and defining the degree of deformity in pathologic angular malalignment of the knee in children. Methods We clinically examined 471 normal Nigerian elementary school children whose ages ranged from three to ten years to determine the clinical tibiofemoral angle and to establish its relationship with body mass index (BMI). Results We found maximum knee valgus of 7.87°at three years, decreasing to 1°at ten years. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 10 publications
5
23
1
1
Order By: Relevance
“…Specifically, there is a negative correlation with height and weight. Axial loading, as represented by BMI, does not contribute towards the increasing magnitude of knee angles in normal, healthy-weight children [23]. Only two studies, by Lin et al [2] and Arazi et al [3], correlated the prevalence of knock knees with sex, height and weight.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, there is a negative correlation with height and weight. Axial loading, as represented by BMI, does not contribute towards the increasing magnitude of knee angles in normal, healthy-weight children [23]. Only two studies, by Lin et al [2] and Arazi et al [3], correlated the prevalence of knock knees with sex, height and weight.…”
Section: Discussionmentioning
confidence: 94%
“…Both TF and the IM distance appear to be associated with height and weight. Only the study of Bafor et al [23], which was carried out among 471 Nigerian school children aged 3-10 years old, using clinical examination, determined the relationship between TF angle and BMI. By contrast, the correlation with sex and BMI is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to correlate well with the anatomic TFA. 19 , 32 The measurements in this study were assessed for intra-observer variation, which, even though was found to be minimal, may be responsible for the sizable sds noted in each age group and the change in TFA after skeletal maturity. The reliability of this method has also been established in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All anthropometrical and goniometrical measurements were done according to the standard technique: IMD, 13 TFA. 3 Body height was measured using a Harpender metal anthropometer to the nearest 0.1 cm, body mass was measured with minimal clothing to the nearest 0.1kg with a medical electronic scale (A&D Instruments, Ltd, Abingdon, UK), and body mass index (BMI) was calculated (BMI=kg/ m 2 ).…”
Section: Methodsmentioning
confidence: 99%